2012
DOI: 10.1038/ejcn.2012.19
|View full text |Cite
|
Sign up to set email alerts
|

Managing patients with gastrostomy tubes in the community: Can a dedicated enteral feed dietetic service reduce hospital readmissions?

Abstract: BACKGROUND/OBJECTIVES: Post-gastrostomy complications range from 8 to 30%. These complications often occur following discharge into the community and may result in hospital readmission. Our unit previously reported a readmission rate of 23% in 6 months. There is a paucity of data evaluating community gastrostomy management. We therefore aimed to evaluate the benefits of a dedicated dietetic home enteral feed (HEF) team. SUBJECTS/METHODS: Demographic data, gastrostomy complications, readmission rates and HEF te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 25 publications
1
65
0
1
Order By: Relevance
“…There are several ways to improve the life of patients living with a PEG. Kurien et al shows in a large prospective study that dietetic aftercare community service reduce hospital readmissions [32]. This is not surprisingly since Brotherton et al found in semi-structured interviews with PEG patients that issues that was emergent related to the enteral feeding were disturbed sleep, limited ability to go out, limited choice of clothing, difficulties finding feeding places.…”
Section: Discussionmentioning
confidence: 99%
“…There are several ways to improve the life of patients living with a PEG. Kurien et al shows in a large prospective study that dietetic aftercare community service reduce hospital readmissions [32]. This is not surprisingly since Brotherton et al found in semi-structured interviews with PEG patients that issues that was emergent related to the enteral feeding were disturbed sleep, limited ability to go out, limited choice of clothing, difficulties finding feeding places.…”
Section: Discussionmentioning
confidence: 99%
“…Hemos observado que ser portador de gastrostomía implica un mayor riesgo de reingreso, a diferencia de lo observado con sonda nasogástrica. Este hallazgo se puede considerar como un marcador de mayor deterioro físico, aunque también podría interpretarse que un procedimiento que se efectúa como solución a un problema puede convertirse en una fuente de comorbilidad 14 .…”
Section: Discussionunclassified
“…Of these, tube occlusion is one of the most common delayed complications seen, usually incurred as a consequence of drugs or enteral feeds [64,65]. Failure to recognize and instigate prompt treatment for this problem can lead to delays in feeding and receiving medication, as well as more serious complications such as peritonitis, infection, bleeding and possibly death.…”
Section: Complications Of Drug Delivery Via Gastric Access Devicesmentioning
confidence: 99%